KAJIAN ESTETIKA SENI BATIK KONTEMPORER MELALUI KARYA KOLABORASI SENIMAN AGUS ISMOYO-NIA FLIAM - Ernawati, Ernawati (Studi Budaya Nusantara, 2019)
Abstract The purpose of this research is to understand batik art contemporary aesthetics created by collaboration of artists Agus Ismoyo-Nia Fliam. This research use qualitative description method using art criticism and aesthetics approach from meaning and fungction of the work aspect. The result of this research, show that the meaning of batik art contemporary contain aesthetic values include cosmological cultural values that is manifested bt visual form and inspired by nature/cosmos. Symbolic value that is an image that contains the meaning and ethical values or attitudes of a cultured life orientation. Work art has personal and social fungtions. This is important in addressing the work of artists as intangible knowledge, knowledge transfer method by local basis and value of main tradition as a concept of growth in work art.